Synthesis and optical properties of novel Bi2O3–Li2O–Al2O3–TeO2 glasses - Zarzali Shah, Aishah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Hisam, Rosdiyana (Elsevier B.V., 2024)
Quaternary glasses of xBi2O3–20Li2O–5Al2O3–(75-x)TeO2 with varying compositions were produced by melt quenching. The purpose was to investigate their physical and optical characteristics. FTIR analysis was employed to examine the structural features of the glass system, followed by UV–Vis spectroscopy for verification of its optical properties. Density measurements performed with a densitometer revealed a rise from 4.68 g/cm³ to 5.06 g/cm³ as the Bi2O3 concentration increased. The refractive index value elevated from 2.6731 to 2.6975 alongside a notable rise in the Urbach energy range from 0.46 to 0.96 eV. As the amount of Bi2O3 varies from 0 to 5 mol%, there was a corresponding rise in the presence of BiO6 units associated with non-bridging oxygen atoms. This observation coincided with a weakening of the bismuth single bond strength, dropping from 283.54 kJ/mol to 158.71 kJ/mol. The optical transmittance decreases to 0.6518, while the reflection loss increases to 0.2108, with an increase in bismuth concentration from 0 to 5 mol%. As the bismuth content increases, both the polarizability of oxide ions and their optical basicity rise consistently, with polarizability values increasing from 2.9163 to 3.0910 Å3 and optical basicity values climbing from 1.0974 to 1.1297. The calculation of interaction parameters indicated that the inclusion of Bi2O3 in glass samples resulted in a shift from high covalency to ionicity, attributed to Bi2O3 acting as a glass modifier.